Structure Formation as a Process of Mutual Adaptation of a Product and Material - Valeriy Vyrovоу; Svitlana Semenova; Diana Zenchenko; Aleksej Aniskin (Tehnički Glasnik)
The article analyzes the influence of the product geometry on the adaptation processes occurring during the structure formation of building composite materials. One of the main aspects determining the structure formation processes are the boundary conditions depending on the product geometry. It is shown that changing the product geometry significantly affects the distribution of stresses and strains, the formation of inner surfaces of partitions and cracks. Active structure elements, such as internal surfaces of partitions and microcracks, are key participants in the adaptation processes, providing stress redistribution. The applied graphoanalytical method demonstrates the possibility of visualizing and analyzing the distribution of deformations. The methods of image analysis and damage coefficient assessment allow us to quantitatively evaluate the adaptive capabilities of the material. Thus, the geometric parameters of the product determine the processes of structure formation in materials and its performance characteristics along with the formulation and technological factors.